Synovial Gene expression after Hemarthrosis differs between FVIII-deficient mice treated with recombinant FVIII or FVIII-Fc Fusion Protein - Bilgimol Chumappumkal Joseph; Thomas C. Whisenant; Esther J. Cooke; Jenny Y. Zhou; Nicca Falah; Juan Andres De-Pablo Moreno; Annette von Drygalski (PLoS ONE, 2025)
To investigate if FVIII-Fc Fusion protein (FcFVIII) may modulate inflammation and immune stimulation in hemophilic synovium via the Fc-portion of immunoglobulin used for half-life extension we performed gene expression profiling in FVIII-deficient mice. Hemarthrosis was induced by sub-patellar puncture in FVIII-KO mice, + /- periprocedural recombinant human (rh)FVIII,murine (m)FcFVIII, or mIgG2a. Synovium was harvested at baseline and on days (D) 3 and 14, followed by RNA extraction and sequencing, and histological analysis. RNASeq data were processed using standard protocols followed by differential gene expression (DGE) analysis. Functional enrichment analysis generated molecular pathways (KEGG and Reactome). To distinguish between on-target and off-target (related and unrelated to injury/bleed) effects the following groups were compared: i) Baseline vs. injured-saline, ii) injured-saline vs. injured-rhFVIII, iii) injured-saline vs. injured-mFcFVIII. Knee injury in FVIII-KO mice resulted in hemarthrosis, which was prevented by peri-procedural rhFVIII and mFcFVIII treatments. Only a small proportion of genes was affected by FVIII treatment, exhibiting overlap but also distinct differences between both FVIII-preparations. Acutely (D3), mFcFVIII had unique on-target effects related to immune and inflammatory regulation, whereas rhFVIII mostly affected mRNA and protein processing. On day 14, macrophage profiling indicated a transition from M1 to M2, and only mFcFVIII uniquely influenced pathways and genes associated with tissue remodeling and repair. Some mFcFVIII DGE patterns resembled mIgG2a patterns. Synovial vascular remodeling and cartilage health were better with mFcFVIII than rhFVIII. Interestingly, both FVIII-preparations exerted off-target effects on immune system pathways, albeit with temporal differences. These observations provide proof-of-principle that the type of FVIII preparation can influence synovial processes beyond acute hemostasis control, deserving exploration in the setting of joint bleed control in hemophilia.